2006
DOI: 10.1002/bio.890
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐oxidant and pro‐oxidant behaviour of bucillamine

Abstract: Bucillamine (BUC) is used clinically for the treatment of rheumatoid arthritis. Some of the pharmacological action of BUC has been reported as being dependent on the production of reactive oxygen species (ROS). In this paper the reactivity of BUC with superoxide anion radical (O(2) (*-)) generated from potassium superoxide/18-crown-6 ether dissolved in DMSO, hydroxyl radical (HO(*)) produced in the Cu(2+)-H(2)O(2) reaction, peroxyl radical (ROO(*)) from 2,2'-azobis (2-amidino-propane) dichloride decomposition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Bucillamine is a cysteine derivative and functions as an antioxidant by transferring thiol groups to the endogenous glutathione or thioredoxin systems and maintaining them in a reduced state (32,33). Animal studies have shown that bucillamine can attenuate tissue damage during myocardial infarction, cardiac surgery and oxidative injury in reperfusion during organ transplantation (19,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Bucillamine is a cysteine derivative and functions as an antioxidant by transferring thiol groups to the endogenous glutathione or thioredoxin systems and maintaining them in a reduced state (32,33). Animal studies have shown that bucillamine can attenuate tissue damage during myocardial infarction, cardiac surgery and oxidative injury in reperfusion during organ transplantation (19,21,22).…”
Section: Discussionmentioning
confidence: 99%